Analisis Pengaruh Lebar Jalan, Jarak ke Central Business District (CBD) Utama Dan Lokal Terhadap Harga Tanah di Kabupaten Minahasa Utara - Fatoni, Bayu Rizki (PT Literasi Nusantara Publisher, 2025)
This research is to answer the problem of increasing land values in North Minahasa district, which varies both in location and value. The aim of this research is to determine how accessibility (road width) influences the land value of North Minahasa Regency and how location (distance to the main CBD and distance to the local CBD) influences the land value of North Minahasa Regency. This research is associative research using the eviews application. The samples in this research were obtained using a purposive sampling technique with a total of 64 samples for the research period of 2024. The research results show that accessibility (road width), designation and location (distance to the Main CBD and distance to the Local CBD) statistically have a significant effect on land value